Surgical interventions for autogenous arteriovenous fistula aneurysms in hemodialysis patients - Özsin, Kadir Kaan; Sanrı, Umut Serhat; Kahraman, Nail; Toktaş, Faruk; Yavuz, Şenol (The European Research Journal, 2018)
Objectives. The aim of this study was to emphasize the importance of surgical intervention perfotmed before development of arteriovenous fistula (AVF) aneurysm complications. Methods. The patients were categorized into two groups: Patients undergoing elective surgery for autogenous AVF aneurysm were defined as elective group (Group 1), whereas those who underwent emergency surgery due to ruptured aneurysmal fistulas were defined as emergency group (Group 2). All elective cases were evaluated by doppler ultrasonography before surgery. All patients had temporary hemodialysis catheters. In the patients with salvaged fistulas, the fistulas was rested for 1 week. A new fistula was created in patients with not salvaged fistula. Results. A total of 31 patients (54.8% male, mean age: 41.2 ± 14.7 years) were in Group 1 and 7 patients (57.1% male, mean age: 53 ± 9.4 years) were in Group 2. Signiﬁcant difference was observed between two groups in terms of fistula preservation. Salvaged fistulas were significantly higher in the Group 1 than Group 2 (p = 0.003). In Kaplan-Meier curves, cumulative primary AVF patency rates at 1, 3 and 6 months were 96.3%, 81.5%, and 77.8% in Group 1 and 66.7%, 66.7%, and 66.7% in Group 2, respectively (log-rank; p = 0.536). Conclusions. Consultation of these cases with a cardiovascular surgeon before they reach the rupture stage is an important condition for both the patency of the fistula and the vital risk of the patient.